EVALUATION OF MEASURES TO DETECT MISAPPROPRIATION OF RESOURCES - Anastasiya V. Vasileva (Статистика и экономика)
The article presents the methodological and technical foundations of the study evaluating the effectiveness of measures to detect misuse of resources. The focus is on the algorithm steps to prepare information and conduct calculations to identify the misuse of resources. Units of analysis, conduct a technical and economic performance of the fixed assets and the most important indicators. We consider the use of performance analysis equipment on time and capacity, analysis of indicators of use of the equipment on the number, analysis of the shift index, a general analysis of return on assets, return on assets factor analysis, analysis of the effectiveness of the fixed assets. The algorithm of actions to prepare information and conduct calculations to identify the misuse of resources.